State-of-the-art review on AL amyloidosis in Western Countries: Epidemiology, health economics, risk assessment and therapeutic management of a rare disease - Sabinot, Alice; Ghetti, Gianni; Pradelli, Lorenzo; Bellucci, Stefania; Lausi, Antonella; Palladini, Giovanni (Blood reviews, 2023)
Amyloidosis is the term to define a broad array of rare protein misfolding syndromes. Among them, light chain (AL) amyloidosis is the most common, affecting roughly 10 people per million/year. The core purpose of the present literature review is to shed light on the academic and clinical knowledge on the condition, encompassing its i) epidemiology, ii) economic burden, and iii) quality of life consequences. The areas of interest are Europe and North America. Literature search was primarily performed on Embase® and finally integrated with additional, deemed eligible, sources. Pre-defined PICOS criteria were employed for the inclusion and exclusion processes. A total of 64 studies were comprehensively included in the current literature review as compliant with the inclusion criteria. The results were presented according to the outcomes of interest and eventually triangulated and compared to available literature studies. A broad picture on the main aspects of AL amyloidosis is delivered.